2022
DOI: 10.1002/cam4.5102
|View full text |Cite
|
Sign up to set email alerts
|

A hypoxia‐related lncRNA model for prediction of head and neck squamous cell carcinoma prognosis

Abstract: Background Head and neck squamous cell carcinoma (HNSCC) is one of the most common and highly heterogeneous malignancies worldwide. Increasing studies have proven that hypoxia and related long non‐coding RNA (lncRNA) are involved in the occurrence and prognosis of HNSCC. The goal of this work is to construct a risk assessment model using hypoxia‐related lncRNAs (hrlncRNAs) for HNSCC prognosis prediction and personalized treatment. Methods Transcriptome expression matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Notablely, we found that the patients in high-risk cohort might have a stronger sensitivity to “docetaxel”. Similar studies have shown that the sensibility to “docetaxel” was higher in the high-risk patients in HNSCC based on a hypoxia-related lncRNA model and a cuproptosis-related lncRNA signature 57 , 58 . Wei Zhang et al revealed that lncRNA LINC00184 could promote “docetaxel” resistance and immune escape in prostate cancer cells and lead to an increase in PD-L1 expression 59 .…”
Section: Discussionsupporting
confidence: 55%
“…Notablely, we found that the patients in high-risk cohort might have a stronger sensitivity to “docetaxel”. Similar studies have shown that the sensibility to “docetaxel” was higher in the high-risk patients in HNSCC based on a hypoxia-related lncRNA model and a cuproptosis-related lncRNA signature 57 , 58 . Wei Zhang et al revealed that lncRNA LINC00184 could promote “docetaxel” resistance and immune escape in prostate cancer cells and lead to an increase in PD-L1 expression 59 .…”
Section: Discussionsupporting
confidence: 55%
“…For example, lncRNA HIFCAR/MIR31HG promotes HNSCC progression by modulating the transcriptional activity of HIF1α [ 36 , 37 ]. In addition, Xiang et al reported 14 hypoxia-regulated lncRNA signatures that could be used for prognosis prediction [ 38 ]. USP2-AS1 has been reported to be possibly regulated by MYC [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Multiple studies reported that hypoxia related genes are associated with tumor progression, metastasis and tumor sensitivity to treatments, such as colorectal cancer, lung cancer, pancreatic ductal adenocarcinoma, and brain tumors. [10][11][12][13] As for HNSCC, Xiang et al 14 demonstrated a hypoxia-related lncRNA signature to predict survival and guide personalized clinical treatment. Recently, single-cell RNA sequencing (scRNA-seq) is a powerful tool to explore single-cell expression patterns in bulk tumor tissue, making it possible to understand immune cellular heterogeneity and the relationship between the microenvironment crosstalk and cancer.…”
Section: Introductionmentioning
confidence: 99%